A possibilidade de uma comunidade ética no pensamento de Kant - Almeida, Fabrício Silva de (2022)
The aim of this study is to investigate the argumentative conditions that make it possible to speak of an ethical community in Kant's thought. Starting from the recognition of radical evil and its social unfolding in terms of an ethical state of nature, Kant postulates as a duty the establishment of a union of men under laws of virtue. However, how to think about an ethical community if, at first, the concepts that make it possible seem to have only subjective validity? How can that which is subjective gain the contours of universality that the ethical community demands? This is because, for the idea of a union of men under laws of virtue to be possible, it is necessary to understand how rational faith or moral faith, possessing only subjective validity, opens itself to the communicability of the concept of God. To solve this problem, the study starts from three practical experiences as a condition criterion for the realization of the ethical community, namely, the non-sensitive reciprocal coercion that makesthe public legislation of the community possible, the idea of God as a necessary postulate in view of the reality objective of the law and, finally, the relationship between the invisible and visible churches under the aegis of the concept of agreement.